Public expenditure costs of carers leaving employment in England, 2015/2016. (14th September 2017) - Pickard, Linda; King, Derek; Brimblecombe, Nicola; Knapp, Martin
Abstract: In the context of global population ageing, the reconciliation of employment and unpaid caring is becoming an important social issue. The estimation of the public expenditure costs of carers leaving employment is a valuable measure that is of considerable interest to policy makers. In 2012, the Personal Social Services Research Unit estimated that the public expenditure costs of unpaid carers leaving employment in England were approximately £1.3 billion a year, based on the costs of Carer's Allowance and lost tax revenues on forgone incomes. However, this figure was known to be an underestimate partly because it did not include other key benefits that carers who have given up work to care may receive. This paper presents a new estimate of the public expenditure costs of carers leaving employment. Key sources of information are the 2009/2010 Survey of Carers in Households, 2011 Census and 2015/2016 costs data. As well as Carer's Allowance, the estimate also now includes the costs of other benefits that carers leaving work may receive, namely, Income Support and Housing Benefit. The results show that the estimated numbers of carers who have left employment because of caring have increased from approximately 315, 000 to 345, 000. Due mainly to the inclusion of a wider range of benefits, the public expenditure costs of carers leaving employment in England are now estimated at £2.9 billion a year. The new estimate comprises £1.7 billion in social security benefits paid to people who have left their jobs because of unpaid caring, plus another £1.2 billion in taxes forgone on this group's lost earnings. The paper concludes that, if there was greater public investment in social care, such as "replacement care" to support carers in employment, and fewer carers then left employment, public spending on benefits would be lower and revenues from taxation would be higher.